2020
DOI: 10.1371/journal.ppat.1008741
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-3 enhances neutrophil motility and extravasation into the airways during Aspergillus fumigatus infection

Abstract: Aspergillus fumigatus is an opportunistic mold that infects patients who are immunocompromised or have chronic lung disease, causing significant morbidity and mortality in these populations. While the factors governing the host response to A. fumigatus remain poorly defined, neutrophil recruitment to the site of infection is critical to clear the fungus. Galectin-3 is a mammalian β-galactose-binding lectin with both antimicrobial and immunomodulatory activities, however the role of galectin-3 in the defense ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 57 publications
2
37
0
Order By: Relevance
“…Recently, our group demonstrated that Gal-3 absence promoted increased fungal burden in the lungs and brain of Gal-3 KO mice by C. neoformans [ 16 ]. This increased susceptibility to the C. neoformans infection in the absence of Gal-3 has also been reported in the infections caused by other fungal pathogens, such as A. fumigatus [ 14 ], C. albicans [ 15 ], and P. brasiliensis [ 18 ]. These studies suggest that Gal-3 deficiency is associated with at higher spread of fungal infection and impaired Th1 and/or Th17 antifungal immune response, corroborating our detected downregulated expression of the genes for proinflammatory cytokines, il-1β in the spleen and brain, il-12a in the lungs, and il-12b in the lungs and spleen.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Recently, our group demonstrated that Gal-3 absence promoted increased fungal burden in the lungs and brain of Gal-3 KO mice by C. neoformans [ 16 ]. This increased susceptibility to the C. neoformans infection in the absence of Gal-3 has also been reported in the infections caused by other fungal pathogens, such as A. fumigatus [ 14 ], C. albicans [ 15 ], and P. brasiliensis [ 18 ]. These studies suggest that Gal-3 deficiency is associated with at higher spread of fungal infection and impaired Th1 and/or Th17 antifungal immune response, corroborating our detected downregulated expression of the genes for proinflammatory cytokines, il-1β in the spleen and brain, il-12a in the lungs, and il-12b in the lungs and spleen.…”
Section: Discussionsupporting
confidence: 64%
“…Its absence, under physiological conditions, promotes differentially modulated genes involved in the transcription of beta-glucan, mannose, and chitin-responsive pattern recognition receptors, signal transduction, inflammation, and phagocytosis [ 13 ]. Recent studies have shown that Gal-3 plays important roles in inflammatory processes and immunity during fungal infections [ 14 , 15 , 16 , 17 , 18 , 19 ]. Thus, our objective was to evaluate the influence of Gal-3 on the host’s innate immune response to C. neoformans infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This protein is expressed in immune system cells including monocytes, macrophages, B and T lymphocytes, dendritic cells, eosinophils, and neutrophils [ 41 , 42 ], indicating it plays important roles in regulating the host immune response in physiological and pathological conditions [ 18 ]. In fungal infections like aspergillosis [ 43 ], candidiasis [ 24 ], cryptococcosis [ 22 ], paracoccidioidomicoses [ 23 , 25 ] and histoplasmosis [ 17 ] the influence of Gal-3 was analyzed through the main organs affected by these pathogens such as lungs, spleens and brains. In this study, we conducted expression profiling of genes involved in the host innate immune system in lungs, spleens and brains of Gal-3 KO mice.…”
Section: Discussionmentioning
confidence: 99%
“…23,24 However, excessive inflammatory response-induced accumulation of large numbers of immune cells and cytotoxic substances in the infected site may cause delayed wound healing or tissue damage, resulting in poor prognosis. 25,26 For example, in cystic fibrosis zebrafish, as a result of the enhanced and sustained accumulation of neutrophils at tail fin wounds, the healing area was reduced by 30% compared with normal control, and the reduced wound healing was significantly improved by genetic ablation of neutrophil. 27 Therefore antifungal therapy combined with immunomodulatory therapy is considered to be the most effective strategy to improve the clinical outcome of Aspergillus-related infection.…”
mentioning
confidence: 99%